2021
DOI: 10.1016/j.ijid.2021.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies to SARS-CoV-2 among blood donors in the early months of the pandemic in Saudi Arabia

Abstract: Background: Serologic testing provides better understanding of SARS-CoV-2 prevalence and its transmission. This study was an investigation of the prevalence of antibodies to SARS-CoV-2 among blood donors in Saudi Arabia. Objective: To estimate the seroprevalence of anti-SARS-CoV-2 antibodies among blood donors in Saudi Arabia during the early phase of the COVID-19 pandemic. Methods: Serology results and epidemiological data were analyzed for 837 adult blood donors, with no confirmed SARS-CoV-2 infection, in Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
(65 reference statements)
6
29
1
Order By: Relevance
“…Our findings are also in line with previous studies which showed that early in the pandemic the seroprevalence of Covid-19 in blood donors or other nontargeted populations was very low ranging from 0% to 2.0% (Erikstrup et al, 2021, Godbout et al, 2020, Qutob et al, 2020, Xu et al, 2020, Ho et al, 2020, Banjar et al, 2021, Nesbitt et al, 2021Slot et al, 2020, Fiore et al, 2021, Saeed et al, 2021. However other studies especially those from hardly hit communities early in the pandemic showed relatively high rates up to 23% (Percivalle et al, 2020).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are also in line with previous studies which showed that early in the pandemic the seroprevalence of Covid-19 in blood donors or other nontargeted populations was very low ranging from 0% to 2.0% (Erikstrup et al, 2021, Godbout et al, 2020, Qutob et al, 2020, Xu et al, 2020, Ho et al, 2020, Banjar et al, 2021, Nesbitt et al, 2021Slot et al, 2020, Fiore et al, 2021, Saeed et al, 2021. However other studies especially those from hardly hit communities early in the pandemic showed relatively high rates up to 23% (Percivalle et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…Those population-based seroprevalence studies varied in the targeted populations tested and the recruitment strategies used which may explain some of the variation. Among the populations tested are healthy blood donors (Sughayer et al, 2020, Slot et al, 2020, Daniel J. Nesbitt et al, 2021, Gallian et al, 2020, Olariu et al, 2021, Younas et al, 2020, Banjar et al, 2021, Uyoga et al, 2021, Busch and Stone, 2021, Martinez-Acuña et al, 2020, Saeed et al, 2021, Slot et al, 2020, Fiore et al, 2021. Again the seroprevalence among healthy blood donors and other population groups studied varied according to the community tested and the time of testing in terms of the pandemic evolution (Lai et al, 2020, Rostami et al, 2020 In this longitudinal study we aimed to estimate the seroprevalence of Covid-19 among healthy blood donors in Jordan at different points in time to assess the degree of community spread and herd immunity and to further understand the evolution of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings were also in line with previous studies, which showed that early in the pandemic the seroprevalence of COVID-19 in blood donors or other nontargeted populations was very low, ranging from 0% to 2.0% (Erikstrup et al, 2021;Godbout et al, 2020;Qutob et al, 2021;Xu et al, 2020;Ho et al, 2020;Banjar et al, 2021;Nesbitt et al, 2021;Slot et al, 2020;Fiore et al, 2021;Saeed et al, 2021). However, other studies, especially those from hard-hit communities early in the pandemic, showed relatively high rates of up to 23% (Rosenberg et al, 2020;Percivalle et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…These population-based seroprevalence studies varied in the targeted populations tested and in the recruitment strategies used, which may explain some of the variation. Among the populations tested were healthy blood donors (Amorim Filho et al, 2020;Sughayer et al, 2020;Slot et al, 2020;Nesbitt et al, 2021;Gallian et al, 2020;Olariu et al, 2021;Younas et al, 2020;Banjar et al, 2021;Uyoga et al, 2021;Busch and Stone, 2021;Martinez-Acuña et al, 2020;Saeed et al, 2021;Fiore et al, 2021). Again, the seroprevalence among healthy blood donors and other population groups studied varied according to the community tested and the time of testing, in terms of the pandemic evolution (Lai et al, 2020;Rostami et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, these guidelines are preliminary and are subjective to further refinement based on the supply and availability of vaccines. The recommendations were based also on the epidemiology of COVID-19 in KSA [ 11 , 12 ], ethical principles, and vaccination implementation. The available seroprevalence of COVID-19 serology indicates pockets of infection among certain population and certain provinces [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%